In vitro evaluation of the antibacterial effect of various root canal sealers on selected anaerobic bacteria* - Pawińska, Małgorzata; Szczurko, Grzegorz; Kierklo, Anna; Łuczaj-Cepowicz, Elżbieta; Marczuk-Kolada, Grażyna; Leszczyńska, Katarzyna (Journal of Stomatology, 2016)
Aim of the study. To determine and compare the antibacterial activity of various root canal sealers against selected strains of anaerobic bacteria: Fusobacterium nucleatum ATCC 25586, Porphyromonas gingivalis ATCC 33277, Peptostreptococcus anaerobius ATCC 27337. Material and Methods. The materials tested in this study included AH Plus Jet (AH), Apexit Plus (AP), Endomethasone N (EN), Epiphany (EP), GuttaFlow (GF), Roeko Seal Automix (RSA), Sealapex (SP) and Tubliseal (TS). The antibacterial effect of the freshly mixed sealers on the above mentioned strains of bacteria was evaluated with the use of the agar diffusion test. After inoculation with the bacteria and applying the materials, the agar plates were incubated at 37°C for one week in an atmosphere of 5-10% CO2. The results were obtained by measuring the diameter of the growth inhibition zone after 48 h, 72 h, one week (F. nucleatum) or 72 h, 120 h and one week (P. gingivalis, P. anaerobius), and analyzed statistically using one-way analysis of variance (ANOVA) followed by post-hoc Tukey’s test. Results. AH, EN, EP, SP and TS significantly inhibited all the bacterial strains over the experimental period. AP showed a slight suppressive effect on P. gingivalis only. No antimicrobial activity was detected for GF and RSA. Conclusions. The antimicrobial effect of root canal sealers varied considerably depending on the type of material and the tested bacterial species. Most of the sealers demonstrated antibacterial action on the investigated bacteria.